Prevention Of Occupational Diseases In The Healthcare System: Ways To Improve And Develop Preventive Measures (Eurasian Journal of Media and Communications, 2026)
This article examines in detail the prevention of occupational diseases among healthcare workers. It analyzes the causes of these diseases, identifies the main risk factors, and presents methods for improving preventive measures. The study's findings indicate that regular medical examinations, hygiene training, rehabilitation programs, and the introduction of modern technologies can effectively reduce occupational disease rates. The importance of introducing international experience and expanding psychosocial support programs is substantiated